2013
DOI: 10.1080/02508060.2014.847777
|View full text |Cite
|
Sign up to set email alerts
|

Small pumps and poor farmers in Sub-Saharan Africa: an assessment of current extent of use and poverty outreach

Abstract: The expansion of irrigation in Sub-Saharan Africa has been slow. In Asia, the rapid expansion of smallholder irrigation systems was attributed in part to the availability and affordability of motorized pumps. This paper appraises the current extent of pump-based irrigation in Sub-Saharan Africa; profiles the socio-economic and demographic attributes of current pump adopters; and assesses the poverty outreach of small-pump technology. It shows that private smallholder irrigation is practised mainly by the wealt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 7 publications
0
20
0
Order By: Relevance
“…Regarding the implementation of irrigation, needed to enable the diversification into high-value crops, Smith (2004) advised that this would be difficult for poorer farmers in developing countries as it required capital and training and was costly to operate. In fact, Namara, Gebregziabher, Giordano, and De Fraiture (2013) showed that private smallholder irrigation was mainly practiced by the wealthier farmers in his study on sub-Saharan Africa. Asfaw et al (2012) found out that adopters of agricultural technology (pigeon pea) were less poor, and with an unconditional headcount poverty ratio 14.6% lower than nonadopters.…”
Section: Chronic Povertymentioning
confidence: 99%
“…Regarding the implementation of irrigation, needed to enable the diversification into high-value crops, Smith (2004) advised that this would be difficult for poorer farmers in developing countries as it required capital and training and was costly to operate. In fact, Namara, Gebregziabher, Giordano, and De Fraiture (2013) showed that private smallholder irrigation was mainly practiced by the wealthier farmers in his study on sub-Saharan Africa. Asfaw et al (2012) found out that adopters of agricultural technology (pigeon pea) were less poor, and with an unconditional headcount poverty ratio 14.6% lower than nonadopters.…”
Section: Chronic Povertymentioning
confidence: 99%
“…Currently, groundwater use in SSA is more often developed in regions which used to rely on rain-fed agriculture (Namara et al 2013), but it may also take place in a context of surface 51 water irrigation van Soelen 2013). Some anecdotal evidence exists on the impact of groundwater irrigation on WUA management of canal irrigation systems.…”
Section: Wuamentioning
confidence: 99%
“…Women are underrepresented in the use and ownership of small-scale irrigation equipment. Research in Ghana and Zambia suggests that men are more likely to own motorized pumps, and in general pump owners have a significantly higher wealth status (Namara et al 2013).…”
Section: The Complex Challenges Faced By Smallholder Farmersmentioning
confidence: 99%